The third regularized trace formula for the Sturm-Liouville operator with the bounded operator coefficient - Baksi, Oezlem; Adiguezelov, Ehliman (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In this work, we obtain a regularized trace formula for the Sturm-Liouville operator with a bounded operator coefficient given in the finite interval. (C) 2010 Published by Elsevier Ltd
Keywords: Self-adjoint operator; Sturm-Liouville operator; Spectrum; Negative eigenvalues; Asymptotic; Computer Science; Mathematics